Mathematics and Statistics Support Centres: Resources for training postgraduates and others who work in them - Croft, Tony; Grove, Michael (MSOR Connections, 2016)
This article provides a rationale for the focused training of postgraduates (and others) who work in mathematics and statistics support centres. It outlines a format for training that has been found to work well through workshop-style events run at universities around the country over the last five years. Within any form of training there are important topics for discussion and a wealth of resources freely available for those centre managers who wish to develop training for their own tutors. Tutors are in the front line of tackling the lack of confidence and skill deficits of students who arrive at support centres looking for help; tutors who are well-briefed in terms of the challenges they are likely to face and how they can best respond to students who are finding university mathematics and statistics particularly difficult will help to ensure that the services offered genuinely contribute to enhancing the student experience. While training for new mathematics support tutors is important, of equal, if not greater importance is identifying tutors with the right skills and abilities to work in mathematics and statistics support. We conclude by considering the recruitment of postgraduate tutors and by undertaking a brief discussion about the value of training to the tutors themselves including contribution to professional recognition that is gaining increased importance. Further sources of information can be found within Croft and Grove (2011) which forms a training resource pack, Croft, et al. (2013) and in the resources section of the sigma network website (2016) which includes PowerPoint slides and training activities that can be used in, or adapted for, workshops.